Combinatorial effect of fluconazole, itraconazole, and terbinafine with different culture extracts of Candida parapsilosis and Trichophyton spp. against Trichophyton rubrum - Lemes, Thiago Henrique [UNESP]; Nascentes, Julyanna Andrade Silva [UNESP]; Regasini, Luis Octávio [UNESP]; Siqueira, João Paulo Zen; Maschio-Lima, Taiza [UNESP]; Pattini, Veridianna Camilo [UNESP]; Ribeiro, Mariela Domiciano; de Almeida, Bianca Gottardo [UNESP]; de Almeida, Margarete Teresa Gottardo (Springer Nature, 2024)
Onychomycosis is a nail infection caused by dermatophytes, non-dermatophyte fungi, and yeasts, especially Candida species. The present study evaluated the combinatorial effect of different cultured extracts of Candida parapsilosis and Trichophyton mentagrophytes and Trichophyton rubrum with fluconazole, itraconazole, and terbinafine against clinical isolates of Trichophyton rubrum. In addition, investigation of the action of the extracts on the wall or membrane was performed. Pure and mixed cultures of Candida parapsilosis and dermatophytes were filtered through a 0.2-μm membrane and submitted to liquid–liquid extraction using ethyl acetate. After a checkerboard, trial with drugs was performed to evaluate the synergistic interaction with the extract. The results obtained for the minimum inhibitory concentration (MIC) of extracts against the T. rubrum strain in isolation were 500–8000 μg/mL. The MIC range for fluconazole, itraconazole, and terbinafine were 2–32 μg/mL, 0.25–0.5 μg/mL, 0.03–64 μg/mL, respectively. However, when the extract was combined with drugs, the MIC values decreased: extracts 1.9–1000 μg/mL, fluconazole 0.25–4, itraconazole 0.03–0.06 μg/mL, and terbinafine 0.001–0.02 μg/mL. The MIC values of the extracts in the Roswell Park Memorial Institute 1640 medium (RPMI) supplemented with sorbitol did not change, suggesting any action on the cell wall. However, in the presence of RPMI supplemented with ergosterol, MIC values of the extracts increased by up to 2×, indicating action on the fungal cell membrane. A synergistic action was observed between products and drugs, detecting a decrease in MIC values. There is potential and a new therapeutic perspective for fungal control.
Keywords: Antifungal drugs; Candida spp; Onychomycosis; Synergism; Trichophyton spp